Bullseyego 1.0 / Saidatul Akma Hamik … [et al.] - Hamik, Saidatul Akma; Abd Aziz, Norazlin; Hassan, Farihah; Merican, Farah Murni (Division of Research and Industry Linkages, 2017)
Autism or autism spectrum disorder, refers to a range of conditions characterized by challenges with social skills, repetitive behaviors, speech and nonverbal communication, as well as by unique strengths and differences. BullseyeGo 1.0 is a game created for autism children at school. This game is regarded as an innovation in teaching and learning activities which will be able to enhance students fine motorskills. Futhermore, this game helps to attract students focus in teaching activities at school. It is hoped that this BullseyeGo game will serve as a interactive activity for the autism students in understanding basic knowledge used during their teaching and learning at their school. In addition, this BullseyeGo is divided into four (4) components namely, the bullseye, question box, and score sheet.